Pemanfaatan Pencahayaan Alami Pada Renovasi Rumah Tinggal Menghadap Arah Barat - Ibayasid Ibayasid; Sujiati Jepriani; Hatta Musthafa A.P; Bhanu Rizfa Hakim (Jurnal Poli-Teknologi, 2020)
The need for housing is very rapid, especially the type of house growing with several choices of area, namely types 21, 27, 36, 45 to 120m2. In the growing house will be provided land for homeowners to develop the house so it is more feasible. The concept of housing provided by the developer is sometimes incompatible with the concept of utilizing natural lighting because it only emphasizes attractive design and number of units. For this reason, it is necessary to provide a reference for homeowners as a strategy to renovate buildings facing the west so that the utilization of natural lighting remains optimal and meets the measurement of comfort visually. The study will analyze the average lux value or Daylight Levels avarage of natural lighting resulting from the amount of light openings. The analysis will be done is the average value of natural lighting from the location strategy and the amount of light aperture in producing quality lighting in space. The kitchen room and family room are spaces with a high level of activity that require optimal lighting. The most optimal lighting level is the opening type of model 1 with 10% opening in the west, 10% opening in the roof, and 50% in the east. The resulting lighting level is 998.58 lux in clear sky conditions and 849 lux overcast conditions.